Can family determine competition within the college campus? the effect of family background on college students’ human capital accumulation - Chunling Li; Yaping Guo (The Journal of Chinese Sociology, 2023)
Abstract Using the Panel Survey of Chinese University Students, this paper systematically analyzes the effect of family background on the human capital accumulation of college students. This study finds that family background has little influence in elite universities, where the selective elimination effect is a determinant. In nonelite universities, however, family background and cultural reproduction mechanisms have significant influence, although individual efforts also factor in the process. In vocational colleges, neither cultural reproduction nor meritocracy is significantly effective. The universalization of higher education has caused divergence in different types of institutions, sorting college students into different competitive fields with different rules. Both the cultural reproduction mechanism and the selective elimination hypothesis can be identified in all kinds of colleges, but their effect varies in relation to institutional types.